Language Teacher Identity and the Domestication of Dissent: An Exploratory Account. Issue 3 (September 2016) - Morgan, Brian
Abstract : In this article, the notion of dissent refers to a more critical, ideological orientation to advocacy for and by TESOL professionals. The notion of domestication refers to identity‐forming practices in the knowledge base of language teacher education (LTE) and in professional certification processes that potentially displace this critical orientation. After a discussion of field‐internal examples (e.g., epistemic dependencies, Kumaravadivelu, 2012; linguistics applied, Widdowson, 1980; language objectification, Reagan, 2004), the article takes up a specific context of domestication : TESL Ontario's accreditation processes and requirements for the certification of adult instructors of ESL (English as a second language). Examining organizational documents and membership survey data, the article suggests that the framing of advocacy is inadequate for the conditions of underemployment and overqualification in this jurisdiction. The article then suggests an alternative for fostering critical advocacy skills in preservice programming: an Issues Analysis Project, in which teachers identify a "gap" in the field (i.e., pedagogical, ideological) and design a blueprint for action (e.g., advocacy letter, policy statement, workshop, curricular innovation) that potentially offers a resolution. The conclusions take up the broader implications of the study for language teacher identity negotiation as well as the TESOL organization's efforts in promoting advocacy amongst its membership.